PERLINDUNGAN HUKUM TERHADAP NASABAH BANK SYARIAH BERDASAR UNDANG UNDANG PERBANKAN DAN PERATURAN BANK INDONESIA - Mieke Anggraeni Dewi (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2017)
Legal protection of the customers of Bank Syariah Law refers to the Banking Law No. 7 of 1992 concerning Banking as amended by Act No. 10 of 1998, Act namely Syariah Banking Act No. 21 of 2008 concerning Islamic Banking, and Bank Indonesia Regulation (PBI) PBI is 7/7 / PBI / 2005 concerning the settlement of customer complaints and PBI No. 8/5 / PBI / 2006 regarding Banking Mediation. The method used is a normative legal research. The results showed that: (1) To provide legal protection, especially for customers, Act No. 10 of 1998 mandated the establishment of the Deposit Insurance Agency (LPS) and requires each bank to ensure public funds are deposited in the bank in question, (2) Protection law for customers of Bank Syariah as consumer banking services in the event of a dispute, the settlement can be made through arbitration, and (3) Model legal protection of customers divided into three groups: the first group, protecting the interests of the Islamic banks and debtors the second group, the unilateral interests of protecting the interests of Islamic banks, as well as a third group, protecting the interests of debtor unilaterally.